Asymptomatic Massive Cerebral Abscess Following Malignant Cerebral Infarct—Aggressive Surgery—Ray of Hope - Pachiyappan, Jeyaselvasenthilkumar Thotalampatti; Kunjithapatham, Deiveegan; Chinnamuthu, Sekar; Yellapragada, Premchand (Indian Journal of Neurosurgery, 2018)
The aim of this article was to present a rare and potentially life-threatening complication of malignant cerebral infarct turning into a massive cerebral abscess. Cerebral abscess complicating cerebral infarction is rare. Only 13 cases have been reported. Unexplained fever is the presenting symptom. The case presented here is unique, as the patient was totally asymptomatic and the abscess was detected incidentally during surgery. A 42-year-old man with malignant left anterior cerebral artery and middle cerebral artery territory infarct underwent decompressive craniotomy 5 weeks before presenting to the authors’ institution. The patient had features of sunken skin flap syndrome. Therefore, cranioplasty was planned. During surgery, false dura was inadvertently opened due to adherence with pia and pus started coming out. On exploration, approximately 150 mL of pus was evacuated. The whole infarcted brain was seen to be converted into a cavity full of pus. Adequate drainage and debridement were done. Cranioplasty was deferred. The patient was treated with broad-spectrum antibiotics postoperatively, and he recovered well. Cerebrovascular accident (CVA) is one among the common causes for mortality and morbidity worldwide. The infarcted or ischemic brain acts like a fertile ground for the pathogens to grow. Disruption of blood–brain barrier and lack of normal blood flow by the vascular event facilitate microbial seeding and formation of cerebral abscess. Abscess formation following stroke is rare. It could prove to be fatal if misdiagnosed or not properly treated. Uncontrolled fever in a stroke patient should raise the suspicion of this rare complication. A routine contrast computed tomography of the brain prior to cranioplasty may pick up this complication in asymptomatic patients. Conservative treatment alone proves fatal in almost all cases.
Keywords: cerebral abscess; cerebral infarct; meningitis